TO THE QUESTION OF SYNTHESIS AND STANDARDIZATION OF PHARMACOLOGICALLY ACTIVE PYRIDINE AND PYRROLE DERIVATIVES - S. Comesse; Ph. Champetter; Z. M. Sarkissyan; A. O. Karasavidi; E. N. Kirillova; S. Bulangas (Разработка и регистрация лекарственных средств, 2019)
The pilot studies on derivative synthesis based on pyrrolo-pyridine and pyrrolo-pyrrole groups possessing pharmacological activity have been conducted. Domino reactions principle has been used during the studies. The possibility of physico-chemical methods appliance has been studied in order to standardize the obtained chemical compounds. Synthesized benzyl ether 5-tert-butyl-1-benzyl-2,4-dioxohexahydro-1H-pyrrolo[3,2]pyridine-3a,5-(6H)-dicarboxylate and benzyl ether 5-tert-butyl-2,4-dioxo-1-phenethylhexahydro-1H-pyrrolo[3,2c]-3a,5(6H)-dicarboxylate were isolated by column chromatography (adsorbent - silica gel). The purity of products were monitored by TLC (thin layer chromatography) during the purification steps, eluent cyclohexane:acetone=3:2, sorbent on Silufol silica gel plates.